Isidore the Laborer: Costa Rican Religious Cultural Heritage - Bonilla Soto, Luis Carlos (2023)
This research identifies Costa Rican Religious Cultural Heritage around Isidore the Laborer cult in 2 ways. First, it analyzes churches declared as the nation’s cultural architecture heritage, with Saint Isidore title. Second, it studies Saint Isidore sculptures in 75 catholic churches chosen by 3 criteria: 1. catholic churches with Saint Isidore title; 2. catholic churches located in communities, where people prepare anual parades every May in honor of Laborer Saint; 3. catholic churches declared as cultural architecture heritage by the Law 7555 of the Republic of Costa Rica.